Construction process and analysis of the psychometric properties of the Postpartum Posttraumatic Stress Inventory (PTSD-PAR). - Parasi Falcón, Claudia (2023)
This article presents the construction process and analysis of the psychometric properties of the Postpartum Posttraumatic Stress Inventory (PTSD-PAR). This instrument was administered to 360 women who gave birth in a hospital and 317 who were attended in a clinic. The instrument evidences content validity with Aiken coeffcient scores higher than .80. An exploratory factor analysis was carried where a four-factor model was obtained. In the confirmatory factor analysis, adequate indices of goodness of fit of the model were obtained, therefore, the new dimensions of the test are: negative perception of childbirth, altered mood, cognitive impairment that hinders attachment, and altered alert state. The instrument presents high reliability of stability and internal consistency. Finally, there are significant differences in terms of educational levels, so, in addition to the general scale, specific standards were developed.